B cell depletion therapies in autoimmune diseases: Monoclonal antibodies or chimeric antigen receptor-based therapy? - Zhang, Zheng; Xu, Qian; Huang, Liang (Frontiers in Immunology, 2023)
Immune system detects foreign pathogens, distinguishes them from self-antigens and responds to defend human body. When this self-tolerance is disrupted, the overactive immune system attacks healthy tissues or organs and the autoimmune diseases develop. B cells and plasma cells contribute a lot to pathogenesis and persistence of autoimmune diseases in both autoantibody-dependent and autoantibody-independent ways. Accumulating data indicates that treatments aiming to eliminate antibody-secreting cells (B cells or plasma cells) are effective in a wide spectrum of autoimmune diseases. Monoclonal antibodies (mAbs) deplete B cell lineage or plasma cells by signaling disruption, complement-dependent cytotoxicity (CDC) and antibody-dependent cellular cytotoxicity (ADCC). Engineered-T cells armed with chimeric antigen receptors (CARs) have been adopted from field of hematological malignancies as a method to eliminate B cells or plasma cells. In this review, we update our understanding of B cell depletion therapies in autoimmune diseases, review the mechanism, efficacy, safety and application of monoclonal antibodies and CAR-based immunotherapies, and discuss the strengths and weaknesses of these treatment options for patients.